2012
DOI: 10.2174/187153012799279027
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Leptin Receptor Expression in Human Polarized Caco-2/15 Cells

Abstract: Our results suggest that (i) the expression of LEPR in Caco-2/15 cell line is not constitutive; (ii) the agents present in the apical or basolateral medium have different effects on LEPR mRNA and/or protein levels; and (iii) short and long isoforms of LEPR follow different patterns of regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
(95 reference statements)
2
4
0
Order By: Relevance
“…Bars 60 µm (c, i), On the basis of these different distributions, we speculate that the expressions of Ob-R and leptin that were present occasionally and with variable distribution among the samples represent a transient expression, locally induced or modulated by stimuli or physiological conditions of the sample. A similar observation was reported for Ob-R expression in Caco-2/15 cells (Cammisotto et al 2012). On the contrary, we believe that our Ob-R detection on the brush border membrane of the epithelium, which was a constant finding in all samples, may be a constitutive location representing a strategic position for monitoring leptin in the intestinal luminal content.…”
Section: Distribution Of Leptin and Ob-r In The Epithelium Of The Larsupporting
confidence: 87%
See 1 more Smart Citation
“…Bars 60 µm (c, i), On the basis of these different distributions, we speculate that the expressions of Ob-R and leptin that were present occasionally and with variable distribution among the samples represent a transient expression, locally induced or modulated by stimuli or physiological conditions of the sample. A similar observation was reported for Ob-R expression in Caco-2/15 cells (Cammisotto et al 2012). On the contrary, we believe that our Ob-R detection on the brush border membrane of the epithelium, which was a constant finding in all samples, may be a constitutive location representing a strategic position for monitoring leptin in the intestinal luminal content.…”
Section: Distribution Of Leptin and Ob-r In The Epithelium Of The Larsupporting
confidence: 87%
“…For example, in rats, systemic leptin stimulated proliferation of epithelial cells in the right colon but not in the left, whereas intracolonic infusion of leptin did not exert a proliferative effect on colonic epithelial cells and did not modify leptinemia (Aparicio et al 2004). Likewise, experiments with polarized cell lines have provided clear evidence that the effect of leptin critically depends on the apical or basolateral origin of the stimulus (Cammisotto et al 2012).…”
Section: Distribution Of Leptin and Ob-r In The Epithelium Of The Larmentioning
confidence: 99%
“…The differences of apical and basal leptin could be related to differences on the regulation of the leptin receptors in each membrane. In this regard, a recent study has demonstrated in Caco-2 cells that the same stimuli (nutrients, hormones or inflammatory agents) added to the apical or basolateral medium have opposite effects on leptin receptors gene and protein expression [8]. The authors point out that these differences could be explained by the distinct characteristics of the apical and basolateral membrane such as the lipid composition, physicochemical properties and fluidity [16].…”
Section: Discussionmentioning
confidence: 99%
“…The authors point out that these differences could be explained by the distinct characteristics of the apical and basolateral membrane such as the lipid composition, physicochemical properties and fluidity [16]. Moreover, they suggest that the origin of leptin could also be determinant in the response to the hormone, since the luminal exocrine leptin comes from gastric Chief cells while the basal leptin is mainly synthesized in the adipose tissue [8]. Thus, in vivo, the apical membrane is exposed to leptin only during the postprandial periods, whereas the basolateral membrane is continuously exposed to plasma leptin, which may regulate leptin receptors expression in a different way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation